ADOÇÃO DO TARGET COSTING NA CONSTRUÇÃO E SUA APLICAÇÃO EM OBRAS PÚBLICAS: EVIDÊNCIAS DA LITERATURA - Lima, Renan; Santos, Débora de Gois (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Efforts have been made to adapt target costing to civil construction. For public works, there are difficulties due to its peculiar restrictions, such as those linked to legislation. There is, yet, scant research focused on these enterprises, even with previous studies suggesting success in adopting target costing. As the literature on the topic is scarce, this article seeks, through a systematic mapping study (SMS), to identify what is being researched and possible gaps in these researches about target costing in publics works. In the construction of this SMS, an evidence-based approach is sought to respond the research problem. The initial selection led to the discovery of 33 papers from conferences and journals on indexed bases, with an additional 10 publications added latter. The studies, in a similar number, deal with case studies and theoretical questions about the application of target costing to construction. The research focused on the civil construction area, not being extended the application of target costing in other disciplines. However, there is a gap when analyzing target costing for public works, with a few conclusions about adaptation and nothing is talked about the possibility of studies and propositions of a better approach.